Economic Dimension of Crimes against Cultural, Historical and Archaeological Heritage - Nozharov, Shteryo (Research Papers, 2015)
The publication is one of the first studies of the economic dimension of crimes against cultural and archaeological heritage. Lack of research in this area is largely due to irregular global prevalence vague definition of economic value of the damage they cause to society at the national and global level, to present and to future generations. The author uses classical models of Becker and Freeman, by modifying and complementing them with the tools of economics of culture based on the non-use values. The model tries to determine the opportunity cost of this type of crime in several scenarios and based on this to determine the extent of their limitation at an affordable cost to society and raising public benefits of conservation of World and National Heritage.JEL:K42, P37, Z11, L83